Gram-Negative Bacteria Salmonella typhimurium Boost Leukotriene Synthesis Induced by Chemoattractant fMLP to Stimulate Neutrophil Swarming - Golenkina, Ekaterina A.; Galkina, Svetlana I.; Pletjushkina, Olga; Chernyak, Boris; Gaponova, Tatjana V.; Romanova, Yulia M.; Sud’ina, Galina F. (Frontiers in Pharmacology, 2022)
Leukotriene synthesis in neutrophils is critical for host survival during infection. In particular, leukotriene B4 (LTB4) is a powerful neutrophil chemoattractant that plays a crucial role in neutrophil swarming. In this work, we demonstrated that preincubation of human neutrophils with Salmonella typhimurium strongly stimulated LTB4 production induced by the bacterial chemoattractant, peptide N-formyl-L-methionyl-L-leucyl-L-phenylalanine (fMLP), while the reverse sequence of additions was ineffective. Preincubation with bacterial lipopolysaccharide or yeast polysaccharide zymosan particles gives weaker effect on fMLP-induced LTB4 production. Activation of 5-lipoxygenase (5-LOX), a key enzyme in leukotrienes biosynthesis, depends on rise of cytosolic concentration of Ca2+ and on translocation of the enzyme to the nuclear membrane. Both processes were stimulated by S. typhimurium. With an increase in the bacteria:neutrophil ratio, the transformation of LTB4 to ω-OH-LTB4 was suppressed, which further supported increased concentration of LTB4. These data indicate that in neutrophils gathered around bacterial clusters, LTB4 production is stimulated and at the same time its transformation is suppressed, which promotes neutrophil swarming and elimination of pathogens simultaneously.